INTERVENSI PENDIDIKAN KESEHATAN OLEH PERAWAT DALAM PENCEGAHAN STROKE PADA POPULASI RISIKO TINGGI: SEBUAH LITERATURE REVIEW - Mare, Agustina Chriswinda Bura; Manungkalit, Maria (Sekolah Tinggi Ilmu Kesehatan Katolik St. Vincentius a Paulo Surabaya, 2025)
Stroke is a major risk factor for global morbidity and mortality. Lifestyle modification and medication adherence are essential strategies for primary and secondary stroke prevention. Nurse-led interventions have been widely evaluated to improve patient knowledge, adherence, and healthy lifestyle behaviors. This literature review examines recent studies on the effectiveness of nurse-led interventions in lifestyle modification, medication adherence, and stroke prevention. This reviewed literature includes quantitative, qualitative, and mixed-method studies published between 2019 and 2025. Literature searches were conducted through EBSCOhost and Google Scholar databases. Most studies indicate that comprehensive, continuous, and multimodal nurse-led interventions—combining face-to-face sessions, digital communication, and theory-based education (TTM, PMT, SCT, TPB)—significantly improve patient knowledge, medication adherence, and lifestyle behaviors. Family and community support also play a crucial role in maintaining long-term behavior change. However, intervention effectiveness may vary depending on population context, program duration, and intervention methods. Nurse-led interventions are an effective strategy for stroke prevention and management of metabolic syndrome, particularly when implemented in a structured, theory-based manner and supported by social networks. Further research is needed to evaluate long-term effectiveness and adaptation of interventions across diverse local contexts.